Conservative Management of Small Bowel Enterocutaneous Fistulas: Possibilities and Limitations - Milina, Srđan; Nikolić, Marija; Trifunovic, Nemanja; Surla, Dimitrije; Dević, Ana; Trifunović, Jovana (Medical Gazzette, 2026)
Introduction: Enterocutaneous fistulas (ECF) are complex and potentially life-threatening complications characterized by a pathological communication between the gastrointestinal tract and the skin. They most commonly arise as a consequence of abdominal surgical procedures, while spontaneous occurrence is rarer and seen in patients with inflammatory bowel diseases, malignancies, or after radiation therapy. Spontaneous closure is possible but uncommon, depending on a number of clinical and local factors. This paper aims to present the current principles, possibilities, and limitations of conservative treatment of small bowel enterocutaneous fistulas, with a focus on factors influencing their spontaneous closure. Methodology: This is a narrative literature review. The search was conducted in PubMed, Scopus, Web of Science, and Cochrane Library for articles published between 2010 and 2025. Keywords used were: enterocutaneous fistula, conservative management, spontaneous closure, intestinal fistula. Studies in English and Serbian addressing conservative approaches to treating small bowel fistulas were included. Factors influencing the course and outcome of treatment were analyzed. Main findings: Key factors influencing spontaneous closure of ECF include low output (<200 mL/day), absence of infection, good nutritional status, simple anatomical configuration, and a closed abdomen. Conservative therapy includes an individualized nutritional plan, control of sepsis and infection, skin protection with barrier agents, and pharmacological modulation of gastrointestinal secretion (e.g., somatostatin and its analogs). Therapeutic methods such as negative pressure wound therapy and fibrin glue show promising results in selected cases. Conclusion: A detailed understanding of factors affecting spontaneous closure of ECF allows for more precise patient selection for conservative treatment. This approach can not only avoid surgical intervention but also significantly improve outcomes in patients who eventually require surgery. A multidisciplinary approach remains crucial for successful management of these patients.